Pengaruh Penambahan Tepung Kunyit (Curcuma domestica) Sebagai Pengganti Antibiotik Terhadap Perfomans Ayam Broiler - Sadi, Ristasari; kornelius Liat Nuhon, Kornelius; Merpati, Merpati; Kondong, Dortje Janet (Anoa: Journal of Animal Husbandry, 2024)
This study aims to determine the effect of giving turmeric flour (Curcuma domestica) supplements as a substitute for antibiotics on the performance of broiler chickens. This research was conducted under the auspices of the STIPER Santo Thomas Aquinas Livestock Research Program, Jayapura. The design used was a Completely Randomized Design (CRD) consisting of 4 treatments, each treatment was repeated 3 times, the treatment structure was P0 = control (commercial feed), P1 = control + 1% turmeric flour, P2 = control + 1 .5% turmeric flour and P3 = Control + 2.0% turmeric flour. The parameters observed were diet consumption, body weight gain and feed conversion. The data analysis used in this research was Analysis of Variation (ANOVA) and if there were significant differences, a BNT test was carried out using SPSS 16 software. The results showed that the addition of turmeric flour made a significant difference (P<0.05) to feed consumption and weight gain. body, but did not provide a significant difference (P>0.05) to broiler chicken feed conversion. The results of the additional BNT test for weight gain showed that treatment P2 and P3 gave the highest weight gain but did not provide any real difference (P>0.05) but did provide a difference in mortality for P0 and P1. Based on the results of the discussion it can be concluded that administration Turmeric flour supplements as a substitute for antibiotics 1.5% and 2% have the effect of increasing feed consumption, and can increase weight gain in broiler chickens. The addition of 1.5% turmeric flour can increase the feed conversion ability of broiler chickens.